The relationship between family support and compliance of chronic kidney failure patients in undergoing hemodialysis therapy at Ciamis District Hospital - Alda Lidiasari; Nur Rahayuningsih; Tita Nofianti (Faculty of Pharmacy, Universitas Pancasila, 2025)
Chronic kidney disease (CKD) is a persistent and permanent decline in kidney function, disrupting metabolism and fluid and electrolyte balance, resulting in an increase in ureum levels. This study aims to analyze the relationship between family support and compliance of CKD patients in undergoing hemodialysis therapy at Ciamis Hospital. This study is descriptive quantitative using a cross sectional approach with accidental sampling technique in January-March 2025, involving 40 inpatient respondents. Data were collected through the Familly Suppot Scale (FSS) questionnaire to measure family support variables and the Morisky Medication 8-item Adherence Scale (MMAS-8) to see hemodialysis therapy compliance. Data testing was conducted with validity, reliability, and R-Square analysis and T-test using Partial Least Squares (PLS) model. The results showed that all instruments were valid and reliable, with AVE Validity > 0.5, Cronbach Alpha and Composite Reliability > 0.7. R-Square analysis, a combination of five family support variables obtained 88.1% of patients had a high level of compliance in following hemodialysis. The T-test results show that there is a significant relationship between instrumental support, informational support, emotional support, appreciation support and self-esteem support with hemodialysis therapy adherence in CKD patients. This is the role of the family is very important in supporting the patient's adherence to hemodialysis therapy.